PRESSURE INFLUENCE TO EXTRACTION SYSTEM HELICHRYSUM ITALICUM – SUPERCRITICAL CARBON DIOXIDE - Mićić, V.; Jotanović, M. Jotanović; Lepojević, Ž.; Aleksić, V.; Pejović, B. (Journal of Engineering & Processing Management, 2009)
Supercritical fluid extraction (SFE) is an efficient extraction technique for the separation of various organic compounds from herbs, or more generally, from plant materials. As cultivate plant (plant from plantation) Helichrysum italicum from municipality Novi Grad was used in this research. The influence of pressure on total extract yield at flow rate 53.5 dm3 /h (calculated at normal state), for extraction time 3 h was investigated. Extraction was performed by supercritical carbon dioxide at different pressures (80, 150, 250 and 350 bar) and constant temperature of 40°C. The extraction yield increase from 0.35 to 5.71% (g/100g drug) by pressure increasing of supercritical extraction by carbon dioxide (isothermal process, t = 40°C). Essential oil content in obtained CO2 extracts was from 6.70 to 31.12%. The highest content of essential oil was in CO2 extract obtained by extraction of drug at p = 80 bar and t = 40°C (31.12%). Qualitative and quantitative determination of CO2 extracts obtained at pressure of 80 and 350 bar as well as of essential oils obtained from extracts, were performed using GC - MS method. The main component were tritriacontane (27.13%) and nonacosane (13.28%). The dominant component in essential oils obtained from extracts was γ – curcumene (28.27 and 27.42%, respectively).